A Bibliometric Study of Pragmatic Studies in Language Research: Insights and Trend - Dahlan, Sriwahyuni; Gaib, Melaliani; La Aba, La Aba (Journal of English Teaching and Linguistic Issues (JETLI), 2023)
This bibliometric study investigates the development and trends within pragmatic studies in language research over the past five years. Pragmatics, which explores language use in context, including phenomena such as speech acts, implicature, deixis, and conversational strategies, has gained prominence as scholars recognize its importance for effective communication. Using a quantitative bibliometric approach, this study analyzes academic publications from databases like Web of Science, Scopus, and Google Scholar to identify key research themes, influential works, and evolving methodologies in the field. The analysis reveals a significant peak in research activity in 2020, with seven articles published, likely driven by increased interest in communication during the COVID-19 pandemic. The variability in publication numbers across other years suggests that research trends in pragmatics are influenced by broader academic and global contexts. The predominant use of qualitative methods, including observation, attentive reading, and listening, highlights the nuanced nature of pragmatic research, which often involves detailed analysis of language use in media such as films, novels, and dramas. Findings also indicate a focus on speech acts, with twelve out of fifteen articles addressing this topic, while research on EFL learning and pragmatic failure is less represented. Data collection primarily involves observational methods, supported by analysis and interviews, reflecting the complexity of studying pragmatic phenomena. The data analysis techniques mostly include percentage-based methods, with fewer studies employing advanced statistical analyses like ANCOVA. This study underscores the evolving nature of pragmatic research and highlights the need for further exploration in areas such as educational settings and advanced methodological approaches. The insights gained provide valuable guidance for future research and practical applications of pragmatic theories, contributing to a deeper understanding of language use and communication.